Problematika Implementasi Kurikulum Merdeka Di Sekolah: Tantangan Membangun Kualitas Pendidikan - Fatimatuzzahrah Fatimatuzzahrah; Lulu Sakinah; Siti Alikha Alyasari (Jurnal Bintang Pendidikan Indonesia, 2023)
This journal discusses the challenges and ideals in implementing the Independent Curriculum in schools. This research aims to identify the main obstacles faced by teachers and educational institutions in implementing the Independent Curriculum approach. Through qualitative analysis and surveys in various schools, the findings show that while the ideals of the Merdeka Curriculum promote an inclusive approach and are oriented towards active learning, many challenges arise in terms of lack of resources, training and systemic support. The results of this research provide in-depth insight into the efforts needed to maximize the potential of the Independent Curriculum in improving the quality of education at the school level. This study makes a significant contribution in the context of improving and improving the national education system.